Shunt capacitor injection to improve voltage stability in power system / Nur Izzati Zahrawani Embong - Embong, Nur Izzati Zahrawani (2009)
Voltage stability is an important factor to be considered in power system operation and planning since voltage instability would lead to system collapse. Furthermore a stable system contributes to reliability and reduction in system loss. Therefore voltage stability analysis is important in order to identify critical buses to enable certain measures to be taken to avoid any incidence of voltage collapse.